Answer:
![f(x)=(x+1/2)^2 +(- 30.25)](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B1%2F2%29%5E2%20%2B%28-%2030.25%29)
Step-by-step explanation:
In this question we are required to rewrite the given function by using completing the square method.
Completing the square method requires that our given equation can be written in form: ![(a\pm b)^2 = a^2 \pm 2ab +b^2](https://tex.z-dn.net/?f=%28a%5Cpm%20b%29%5E2%20%3D%20a%5E2%20%5Cpm%202ab%20%2Bb%5E2)
SO, we have to transform our equation according to above format.
Since our equation is
, we will transform it into
because the middle term of given equation has + sign.
![x^2+x-30=0\\x^2+x=30\\x^2 + 2(x)(1/2) + (1/2) ^2 = 30 + (1/2)^2](https://tex.z-dn.net/?f=x%5E2%2Bx-30%3D0%5C%5Cx%5E2%2Bx%3D30%5C%5Cx%5E2%20%2B%202%28x%29%281%2F2%29%20%2B%20%281%2F2%29%20%5E2%20%3D%2030%20%2B%20%281%2F2%29%5E2)
We have introduced (1/2)^2 on both sides of the equation to gain the required form.
![(x+1/2)^2 = 30.25\\(x+1/2)^2 - 30.25 = 0\\f(x) = (x+1/2)^2 +(- 30.25)](https://tex.z-dn.net/?f=%28x%2B1%2F2%29%5E2%20%3D%2030.25%5C%5C%28x%2B1%2F2%29%5E2%20-%2030.25%20%3D%200%5C%5Cf%28x%29%20%3D%20%28x%2B1%2F2%29%5E2%20%2B%28-%2030.25%29)
Our answer is ![f(x)=(x+1/2)^2 +(- 30.25)](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B1%2F2%29%5E2%20%2B%28-%2030.25%29)